Examining the role of various factors and experiences in technology integration a description of a professional model - Cenzon, Carlos G. (Ann Arbor Michigan ProQuest LLC, 2008)
A mixed-design study investigated relationships among several factors and descriptions of particular experiences of graduates in a professional development program in technology integration. The quantitative aspect examined how demographic variables (age, gender, number of years as an educator, and length of time since graduating from the program) and attitudes (about technology and learning, technology tools, and instructional strategies) contribute to practice of technology integration. It also examined differences in attitudes, practices, and support on technology integration between early and recent graduates. The qualitative aspect explored participants' thoughts on the program's best and least helpful attributes and changes they think could make the program better. Results showed that attitudes toward technology tools in addition to attitudes and use of technology-enhanced instructional strategies significantly contribute to the use of technology tools. Second, attitudes and use of technology tools as well as attitudes about technology-enhanced instructional strategies significantly contribute to the use of technology-enhanced instructional strategies. Third, weak but significant differences were found between early and recent graduates on two aspects. Earlier graduates value technology-enhanced instructional strategies and take college or university courses to keep up-to-date slightly more than recent graduates. Qualitative analyses revealed that the use of authentic problems, collaboration, and hands-on approach were considered the best attributes of the program. The greatest challenges were time factor, readings, and lack of differentiation. In terms of changes to the program, the top answer was to have no changes, followed by more differentiation, and the learning of more skills and technologies. This study confirmed the relative success of constructivist strategies in implementing professional development in technology integration. The conclusion includes recommendations for practice and further study.
Thesis (Ph.D.)--George Mason University, 2008.
Keywords: Educational technology -- Education (Higher)